Factors Associatedwith with the Development of Striae Gravidarum - Soleimani, Mohammad Ali; Mohammad Rezaei, Zhila; Sharif Nia, Hamid; Bozorgzad, Parisa; Hekmat Afshar, Mitra (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Striae Gravidarum is one of the common skin changes during pregnancy. There are several risk factors for striae development. The aim of this study was to survey of associated factors with the development of striae gravidarum. Materials and methods: A convenience sample of 325 primiparous women were assessed during the immediate postpartum period for evidence of SG. Data were collected by a questionnaire and physical examination. The presence and and severity of striae was evaluated by Davey’s score. To determine the possible risk factors for the development of SG, characteristics of women with and without striae were compared using chi square test, independent t test and logistic Regression. Findings: In 182 (81.3%) of participants striae gravidarum was developed. Development of SG in 174 of 182 women (95.6%) was on the abdomen, 110 of 182 (60.4%) was on the thighs and in 74 of 182 (40.6%) SG was developed on the breasts during their pregnancy. Mean and SD of Davey score in breast, abdomen and thighs were (1.08 ± 1.55), (4.31 ± 2.21) and (1.76 ± 2.02) respectively. Family history of SG in mother, weight gain and body mass index during pregnancy and newborn weight, were signifi cantly associated with the development of SG. Conclusions: This study showed that genetic factors (family history of striae gravidarum) and physical factors (weight gain and body mass index during pregnancy) may have a significant role in development of striae gravidarum. Therefore, conducting studies in the future to identify how these factors can cause striae gravidarum seem to be helpful. Keywords: Striae Gravidarum, Striae, Prevalenceو Risk Factors. REFERENCES Atwal GS ML, Griffiths CE, Polson DW (2006) Striae Gravidarum in Primipae. British Journal of Dermatology . 155(5) 965-9. Chang AL Agredano YZ Kimball AB (2004) Risk Factors Associated with Striae Gravidarum. Journal of the American Academy of Dermatology , 51(6) 881-5. Cunningham FG, Bloom SL, Leveno KJ (2010) Williams Obstetrics 23rd Ed. New York: McGraw-Hill. Davey CM(1972) Factors Associated with the Occurrence of Striae Gravidarum. An International of Journal Obstetrics and Gynecology . 79(12) 1113-4. Durmazlar SPK, Eskioğlu F(2009) Striae Gravidarum: Associated Factors in Turkish Primiparae. Journal of the Turkish Academy Dermatology , 3(4) 93401a. Fitzpatrick TB(1988) The Validity and Practicality of Sun-Reactive Skin Types I Through VI. Archives of Dermatology . 124(6) 869. Gabbe S.G. NJR, Simpson J.L (2002) Obstetrics: Normal and Problem Pregnancies . 4th Ed. New York (NY): Churchill Livingstone. Ghasemi A, Gorouhi F, Rashighi Firoozabadi M, Jafarian S, Firooz A (2007) Striae Gravidarum: Associated Factors. Journal of the European Academy of Dermatology and Venereology . 21(6) 743-6. Lerdpienpitayakul R, Manusirivithaya S, Wiriyasirivaj B, Lorwatthanasirikul J(2009) Prevalence and Risk Factors of Striae Gravidarum in Primiparae. Thai Journal of Obstetrics and Gynaecology . 17(2) 70-9 Liu D(1974) Letter:Striae gravidarum. Lancet. 1(7858) 625. McDaniel DH, Ash K, Zukowski M(1996) Treatment of Stretch Marks with the 585-nm Flashlamp-Pumped Pulsed Dye Laser. Dermatologic Surgery . 22(4) 332-8. Osman H, Rubeiz N, Tamim H, Nassar AH (2007) Risk Factors for the Development of Striae Gravidarum. American Journal of Obstetrics and Gynecology . 196(1) 62 e1-5. Ratree JO, Titapant V, Chuenwattana P, Tontisirin P (2008) Prevalence and Associate Factors for Striae Gravidarum. Journal of the Medical Association of Thailand = Chotmaihet Thangphaet . 91(4) 445-51. Salter SA, Batra RS, Rohrer TE, Kohli N, Kimball AB (2006) Striae and Pelvic Relaxation: Two Disorders of Connective Tissue with a Strong Association. Journal of Investigative Dermatology . 126(8) 1745-8. Shuster S. 1979. The Cause of Striae Distensae. Acta Dermato-Venereologica Supplementum , 59(85) 161. Thomas R, Liston W(2004) Clinical Associations of Striae Gravidarum. Journal of Obstetrics & Gynecology . 24(3) 270-1. Wade TR, Wade SL, Jones HE (1978) Skin Changes and Diseases Associated with Pregnancy. Obstetrics & Gynecology .52(2) 233-42. Watson R, Parry E, Humphries J, Jones C, Polson D, Kielty C, et al (1998) Fibrillin Microfibrils Are Reduced in Skin Exhibiting Striae Distensae. British Journal of Dermatology . 138(6) 931-7. Wong RC, Ellis CN. 1984. Physiologic Skin Changes in Pregnancy. Journal of the American Academy of Dermatology , 10(6) 929-40.